Preparation of LiMn2O4 Nanorods and Nanoparticles for Lithium-ion Battery Applications. (2016) - Hariprasad, K.; Naresh, N.; Nageswara Rao, B.; Venkateswarlu, M.; Satyanarayana, N.
Abstract: Spinel LiMn2 O4 nanorods were prepared by rapid two steps synthesis process, which involves a novel microwave hydrothermal synthesis and followed by a solid-state reaction. LiMn2 O4 nanoparticles were prepared by pechini process. X-ray diffraction (XRD) studies of the prepared samples confirmed the formation of crystalline pure spinel phase of LiMn2 O4 nanoparticles and nanorods. Fourier transform infrared (FTIR) studies of the prepared samples confirmed the formation of the LiMn2 O4 structured nanoparticles and nanorods. Scanning electron microscopy (SEM) micrographs of the prepared samples showed the formation of the LiMn2 O4 nanorods and nanoparticles. Electrical conductivities studies of LiMn2 O4 nanorods and nanoparticles were studied through impedance spectroscopy measurements.